Cardiovascular Disease, Volume 2: Molecular Medicine
DOI: 10.1385/1-59745-213-0:279
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis Assays

Abstract: A large number of methods devoted to the identification of apoptotic cells and the analysis of the morphological, biochemical, and molecular changes that take place during this universal biological process have been developed. Apoptotic cells are recognized on the basis of their reduced DNA content and morphological changes that include nuclear condensation and which can be detected by flow cytometry (sub-G1 DNA content), Trypan Blue, or Hoechst staining. Changes in plasma membrane composition and function are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 0 publications
2
28
0
Order By: Relevance
“…Our studies on the nuclear morphology of BAEC revealed that IB05204 induces nuclear changes, characterized by chromatin condensation and nuclear fragmentation. This result was also confirmed by the monitoring of the cell cycle distribution, showing an increase of the percentage of cells with sub-diploid DNA content, a hallmark of an apoptotic cell population (45). In contrast, a similar dose of IB05204 did not cause any observable effect in the cancer cell lines HCT-116 and HT1080.…”
Section: Discussionsupporting
confidence: 52%
“…Our studies on the nuclear morphology of BAEC revealed that IB05204 induces nuclear changes, characterized by chromatin condensation and nuclear fragmentation. This result was also confirmed by the monitoring of the cell cycle distribution, showing an increase of the percentage of cells with sub-diploid DNA content, a hallmark of an apoptotic cell population (45). In contrast, a similar dose of IB05204 did not cause any observable effect in the cancer cell lines HCT-116 and HT1080.…”
Section: Discussionsupporting
confidence: 52%
“…The experiment was then repeated, and the proportion of apoptotic cells in the PiZ mouse livers (4 individual PiZ mouse livers were examined) was then determined with fluorescence-activated cell sorting through the counting of the cells on the basis of the detection of phosphotidyl serine changes in the outer membrane by fluorescein isothiocyanate-conjugated annexin-V antibody binding, a known marker for cells committed to apoptosis. 9,12 The result in Fig. 1E shows an increase in the proportion of apoptotic cells in the PiZ mouse liver directly correlated to the increased intracellular accumulation of a1AT mutant Z polymerized protein.…”
Section: Resultsmentioning
confidence: 87%
“…(D) Cell cycle profiles for the cells represented in A showing a shift towards G 1 with either eIF4G or eIF4G+Ofs knockdown. eIF4A knockdown caused an increase in the percentage of cells with sub-G 1 DNA content, normally indicative of apoptotic cells (Oancea et al, 2006). (E) Summary of cell cycle profiling showing rescue by GFP-Ofs and GFP-eIF4G, but not by GFP alone.…”
Section: Research Articlementioning
confidence: 99%